Pengaruh Citra Destinasi, Fasilitas Wisata terhadap Minat Berkunjung Ulang (Studi kasus Wisatawan Pantai Klayar Pacitan) - Siti Lestari; Ima Kristina Yulita; T Handono Eko Prabowo (EXERO : Journal of Research in Business and Economics, 2022)
This study aims to determine: 1) the influence of the image of destinations and tourist facilities simultaneously on the interest in revisiting at Klayar Beach Pacitan, 2) the influence of the image of the destination on the interest in revisiting at Klayar Beach Pacitan, 3) the influence of tourist facilities on the interest in revisiting at Klayar Beach Pacitan. The population in this study are all tourists who have visited and are currently visiting Klayar Beach. The sampling technique used was purposive sampling. Data was obtained by distributing questionnaires to 100 respondents. The data analysis technique in this study was multiple linear regression. analysis using the IBM SPSS Statistic 25 application. The results showed that: 1) the image of the destination, tourist facilities simultaneously affected the interest in returning to Klayar Beach, Pacitan, 2) the image of the destination partially affected on interest in revisiting Klayar Beach Pacitan, 3) tourism facilities partially affect interest in revisiting Klayar Beach Pacitan.